The waiting room [videorecording (DVD)] - Nicks, Peter; Nicks, Peter (Docurama ; Cinedigm Entertainment Corp., 2013)
A character-driven documentary film that goes behind the doors of an American public hospital struggling to care for a community of largely uninsured patients. Young victims of gun violence take their turn alongside artists and small business owners who lack insurance. The film weaves the stories of several patients-as well as the hospital staff charged with caring for them-as they cope with the complexity of the nation's public health care system, while dealing with a national recession.